A mathematical model of metabolism and regulation provides a systems-level view of how Escherichia coli responds to oxygen - Ederer, Michael; Steinsiek, Sonja; Stagge, Stefan; Rolfe, Matthew; Ter Beek, Alexander; Knies, David; Teixeira de Mattos, Joost; Sauter, Thomas; Green, Jeffrey; Poole, Robert; Bettenbrock, Katja; Sawodny, Oliver (Frontiers in Microbiology, 2014)
The efficient redesign of bacteria for biotechnological purposes, such as biofuel production, waste disposal or specific biocatalytic functions, requires a quantitative systems-level understanding of energy supply, carbon and redox metabolism. The measurement of transcript levels, metabolite concentrations and metabolic fluxes per se gives an incomplete picture. An appreciation of the interdependencies between the different measurement values is essential for systems-level understanding. Mathematical modeling has the potential to provide a coherent and quantitative description of the interplay between gene expression, metabolite concentrations and metabolic fluxes. Escherichia coli undergoes major adaptations in central metabolism when the availability of oxygen changes. Thus, an integrated description of the oxygen response provides a benchmark of our understanding of carbon, energy and redox metabolism. We present the first comprehensive model of the central metabolism of E. coli that describes steady-state metabolism at different levels of oxygen availability. Variables of the model are metabolite concentrations, gene expression levels, transcription factor activities, metabolic fluxes and biomass concentration. We analyze the model with respect to the production capabilities of central metabolism of E. coli. In particular, we predict how precursor and biomass concentration are affected by product formation.